Strategi Perbaikan Sistem Pernapasan pada Pasien PPOK Melalui Terapi Komplementer - Rohmah, Ulfa Nur; Yari, Yarwin; Ramba, Hardin La; Suarti, Ni Made; Prawitasari, Shinta (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2024)
Introduction: Complementary therapies have now become part of innovations that play a role in COPD patients so that they become essential as treatment supporters that have benefits, especially in improving the respiratory system, especially in COPD patients who return after exacerbations. Objectives: This study aims to determine strategies in improving the respiratory system in COPD patients through comprehensive therapy. Methods: Selection of articles using PRISMA guidelines using databased in the form of Scopus, CINAHL, Cochrane, ProQuest so that a narrative review is formed. The criteria for eligible articles include RCT or non-RCT with pre-test and post-test design, published between 2018-2023, full text, English, not considering control group, not studies related to drugs to treat diseases and complications. Results: The results obtained in this study after adjusting to the study criteria were 9 feasible articles. Complementary therapies in COPD patients can include breathing techniques, suppression techniques, music therapy, energy muscle techniques, and pulmonary rehabilitation. The complementary therapies in the study had almost mostly an impact on improving the respiratory system status of COPD patients Conclusion: Complementary therapy of COPD patients can be a holistic approach that must be a concern that can be implemented into various stages of treatment of COPD patients by involving multidisciplinary teams so that there is defense and improvement of the respiratory system